Chemokine and Cytokine Cascade Caused by Skewing of the Th1-Th2 Balance Is Associated with High Intracranial Pressure in HIV-Associated Cryptococcal Meningitis - Lijun Xu; Yongzheng Guo; Yizhou Zhao; Yufan Xu; Xiuming Peng; Zongxing Yang; Ran Tao; Ying Huang; Yan Xu; Yaokai Chen; Biao Zhu (Mediators of Inflammation)
Purpose. Serum cytokines/chemokines play important roles in cryptococcal meningitis, but it is unclear whether cytokines/chemokines in cerebrospinal fluid (CSF) contribute to high intracranial pressure (HICP) in HIV-associated cryptococcal meningitis (HCM). Methods. CSF cytokines/chemokines were assayed in 17 HIV-uninfected patients, 26 HIV-infected patients without CNS infection, and 39 HCM patients at admission. Principal component analysis and correlation and logistic regression analyses were used to assess the relationships between these parameters. Results. The CSF Th1, Th2, and macrophage cytokines showed an obvious increase in HCM patients as compared to the HIV-uninfected patients and HIV-infected patients without CNS infection. CSF IL-6, GM-CSF, and IL-8 were positively correlated with CSF fungal burden. Serum CD4 count, CSF Th1 cytokines (TNF-α, TNF-β, IL-12, IL-1β, and INF-α2), and Th2 cytokines (IL-5 and IL-6) were closely related to cryptococcal meningitis. Furthermore, both Th1 cytokines (TNF-α, TNF-β, INF-γ, and IL-12) and Th2 cytokines (IL-4 and IL-10) contribute to HICP. Conclusion. Overall, the present findings indicated that both pro- and anti-inflammatory cytokines of Th1, Th2, and macrophage origin contributed to the development of HCM. Specifically, the chemokine and cytokine cascade caused by skewing of the Th1-Th2 balance and reduced CD4 count were found to be important contributors to HICP. Summary. Our research suggested that chemokine and cytokine cascade caused by skewing of the Th1-Th2 balance in HIV-infected patients played more important role than Cryptococcus numbers and size in CSF on the development of high intracranial pressure in HIV-associated cryptococcal meningitis, providing a new understanding of mechanisms of HCM.